The effect of static stretching, mini-band warm-ups, medicine-ball warm-ups, and a light jogging warm-up on common athletic ability tests - Christensen, K.; Bond, C. W.; Napoli, R.; Lopez, K.; Miller, J.; Hackney, K. J. (International Journal of Exercise Science, 2020)
Proper warm-up is important for facilitating peak athletic performance and reducing injury risk; yet, warm-up procedures vary considerably amongst coaches and athletes. The purpose of this study was to assess the effect of a static stretching, medicine-ball, and mini-band warm-ups relative to a light jogging warm-up only on athletic ability test performance. It was hypothesized that static stretching would negatively affect performance, while medicine-ball and mini-band warm-ups would positively affect performance relative to light jogging only. Twelve female collegiate soccer players (19.3 ± 1.2y, 65.2 ± 7.5kg, 1.67 ± 0.07m) participated in this study. Athletes completed each warm-up protocol and all of the athletic performance tests over four sessions in asemi-randomized, counterbalanced order. An omnibus MANOVA with vertical jump height, medicine ball throw distance, 10m and 20m sprint time, and T-test time as the dependent variables was not significant indicating that warm up did not have an effect on subsequent athletic ability test performance [Wilks` Lambda = 0.64, F(15,110) = 1.28, p= 0.23, Eta2= 0.14]. Static stretching warm-up did not negatively influence athletic potential compared to mini-band and medicine ball warm-ups, though the most optimal warm-upis likely athlete specific.KEY WORDS: Soccer, athletic performance, vertical jump, short sprints, medicine ball thro